SEG Technical Program Expanded Abstracts 2004 2004
DOI: 10.1190/1.1851282
|View full text |Cite
|
Sign up to set email alerts
|

Predicting seal risk and charge capacity using chimney processing: Three Gulf of Mexico case histories

Abstract: This paper describes how seismically derived 3D chimney volumes or "cubes" can be used to assess seal risk in exploration wells in the shelf and upper slope of the Gulf of Mexico. For this evaluation four examples of hydrocarbon accumulations with effective seals, one example of a breached seal, and one untested prospect are evaluated. From these examples, we have developed criteria to quantify the seal risk and charge capacity by differentiating different types of chimneys and other information. Such criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Recent works by Ligtenberg and Thomsen (2003), Heggland (2005), Ligtenberg (2005), Walraven et al (2005a), and Roberts et al (2006) showed that 3-D seismic data are highly successful at detecting hydrocarbon migration pathways to or from a reservoir as well as possible expulsion sites and as such can be used to investigate the fluid transport properties of faults. Results of up-fault leakage will most likely affect the bulk proprieties of a rock body (Judd et al, 1992) in the fault zone or within adjacent discharge sites; it will then produce anomalies such as acoustic turbidity zones capturing gas chimneys, shallow seismic anomalies, and bright spots related to gas pockets (Kaluza and Doyle, 1996;Heggland, 2002;Aminzadeh et al, 2004;Walraven et al, 2005b;Cartwright et al, 2007;Halliday et al, 2008).…”
Section: Up-fault Remigration Indications From 3-d Seismic Datamentioning
confidence: 98%
“…Recent works by Ligtenberg and Thomsen (2003), Heggland (2005), Ligtenberg (2005), Walraven et al (2005a), and Roberts et al (2006) showed that 3-D seismic data are highly successful at detecting hydrocarbon migration pathways to or from a reservoir as well as possible expulsion sites and as such can be used to investigate the fluid transport properties of faults. Results of up-fault leakage will most likely affect the bulk proprieties of a rock body (Judd et al, 1992) in the fault zone or within adjacent discharge sites; it will then produce anomalies such as acoustic turbidity zones capturing gas chimneys, shallow seismic anomalies, and bright spots related to gas pockets (Kaluza and Doyle, 1996;Heggland, 2002;Aminzadeh et al, 2004;Walraven et al, 2005b;Cartwright et al, 2007;Halliday et al, 2008).…”
Section: Up-fault Remigration Indications From 3-d Seismic Datamentioning
confidence: 98%
“…In petroliferous basins, gas chimneys provide clues for a better understanding of spatial and temporal linkages between various storeys of the petroleum system (Meldahl et al ., ; Løseth et al ., ). As summarized by Ligtenberg (), they can provide information as to the type of fluid activity in source rocks (Ligtenberg & Thomsen, ), top‐seal integrity analysis (Heggland, ; Walraven et al ., ; Cartwright et al ., ), and whether the potential target is charged or leaking (Heggland et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Leakage from potential reservoirs, which may provide better insight in the lateral and top seal quality (Walraven et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gas chimneys and fluids migrating along faults and reaching potential reservoir formations, thereby providing information about whether a prospect is charged or not (Heggland et al , 2000, 2001). Leakage from potential reservoirs, which may provide better insight in the lateral and top seal quality (Walraven et al , 2004). Leakage from these potential reservoirs to shallower levels and charging shallow sands, thus indicating the presence of shallow gas drilling hazards (e.g.…”
Section: Introductionmentioning
confidence: 99%